Analysis of Product Quality, Brand Image and Service Quality on Purchasing Decisions (Marketing Management Literature Review) - Aprelyani, Siska (Siber International Journal of Education Technology (SIJET), 2024)
Literature Review The Influence of Product Quality, Brand Image and Quality of Service on Purchasing Decisions is a scientific article used to build a research hypothesis on the influence between variables that will be used in further research. The method of writing a literature review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other online media. The results of this article are: 1) Product Quality influences Purchasing Decisions; 2) Brand Image influences Purchasing Decisions; 3) Quality of Service influences Purchasing Decisions. Apart from these 3 exogenous variables that influence the endogenous variable of Purchasing Decisions, there are still many other factors including buying interest, promotion, price.